Are Expectations the Missing Link between Life History Strategies and Psychopathology? - Kavanagh, Phillip S.; Kahl, Bianca L. (Frontiers in Psychology, 2018)
Despite advances in knowledge and thinking about using life history theory to explain psychopathology there is still a missing link. That is, we all have a life history strategy, but not all of us develop mental health problems. We propose that the missing link is expectations – a mismatch between expected environmental conditions (including social) set by variations in life history strategies and the current environmental conditions. The mismatch hypothesis has been applied at the biological level in terms of health and disease and we believe that it can also be applied more broadly at the psychological level in terms of perceived expectations in the social environment and the resulting distress—psychopathology—that manifests when our expectations are not met.